Control of hierarchic slope-break zones on grain shoal reservoirs and favorable exploration zones: A case study of Cambrian Xixiangchi Formation in the south slope of Leshan-Longnüsi paleouplift, Sichuan Basin, SW China - Tao MA; Xiucheng TAN; Bing LUO; Yuan HE; Qiang XU; Maoxuan HUANG; Qirui LI; Hongyu LONG; Anping HU (Petroleum Exploration and Development)
Based on 2D and 3D seismic data and well logging data, this paper studies the distribution of well-seismic stratigraphic filling and shoal controlled reservoirs of Upper Cambrian Xixiangchi Formation in the south slope of Leshan-Longnüsi paleouplift in the Sichuan Basin, to reveal the genetic relationship between stratigraphic filling, paleogeomorphology and large-scale grain shoal. (1) The Xixiangchi Formation in the study area is overlapped and filled gradually to the Leshan-Longnüsi paleouplift, but gets thin sharply due to truncation only near the denudation pinch-out line of the paleouplift. Two overlap slope break belts and one erosion slope break belt are identified, and the Xixiangchi Formation is divided into 4 members from bottom to top. (2) The filling pattern of the overlapping at the base and erosion at the top indicates that the thickness of Xixiangchi Formation can reflect the pre-depositional paleogeomorphology, and reveals that the studied area has a monoclinal geomorphic feature of plunging to southeast and being controlled by multistage slope break belts. (3) The large-scale grain shoals and shoal controlled reservoirs are developed longitudinally in the third and fourth members of the Xixiangchi Formation, and laterally in the vicinity of the multistage overlap slope break belts. (4) Overlap slope break belts are closely related to northwest trending reverse faults. The western margin of the South China Plate converging with the Qiangtang-Himalaya massif in the middle -late Cambrian resulted in the rapid uplift of the northwestern margin of the Yangtze Plate and expanding toward southeast, leaving gradually plunging multistage slope breaks and large-scale northeast grain shoal reservoir belts. Considering oil and gas test results, it is predicted that the favorable exploration zone of the grain shoal controlled reservoirs covers an area of 3 340 km2.